Understanding unplanned readmissions for children undergoing surgery in a single pediatric general surgical department - Chao Zheng; Hong Zhou; Hai Zhu; Bailin Chen; Lin Qiu; Chunbao Guo (BMC, 2019)
Abstract Background The aim of the current research was to investigate the unplanned readmission rates and identify the risk factors of unplanned readmissions in pediatric general surgical specialties. Methods A retrospective review of unplanned readmissions following initial surgery from July 1, 2010, to June 30, 2017, in the general surgical specialties at an academic tertiary care hospital was performed. The main outcome of interest was unplanned readmission rates, the common causes for readmission. The risk factors involved in the unplanned readmissions were further investigated using univariate and multivariate analyses. Results Of the 3263 patients who underwent surgery and discharge, 176 (9%) were unplanned readmissions. The most frequent surgical operation related to readmission was appendectomy, and the common readmission causes were associated with treatment of gastrointestinal complaints/complications. Multivariable analysis demonstrated that emergency surgery (p = 0.016, odds ratio [OR] = 2.73; 95% CI = 1.35-6.19), major complications (p = 0.042, OR = 2.43; 95% CI = 1.12-4.71) and the initial hospital length of stay (p = 0.036, OR = 3.46; 95% CI = 1.67-7.53) were independent risk factors for readmission. Conclusions This study identified potential risks for readmission, which should be targeted for interventions to improve quality and resource allocation.